Safe enough : and other stories - Child, Lee (New York The Mysterious Press, 2024)
Meticulously plotted and packed with Child's trademark action and suspense, a collection of 20 short stories shows the author's mastery of the short form, and they've never been gathered before now.
The bodyguard -- The greatest trick of all -- Ten keys -- Safe enough -- Normal in every way -- The .50 solution -- Public transportation -- Me & Mr. Rafferty -- Section 7 (a) (operational) -- Addicted to sweetness -- The bone-headed league -- I heard a romantic story -- My first drug trial -- Wet with rain -- The truth about what happened -- Pierre, Lucien, and me -- New blank document -- Shorty and the briefcase -- Dying for a cigarette -- The snake eater by the numbers.
114997
Keywords: Police -- Fiction; Criminals -- Fiction; Detective and mystery fiction; Thrillers (Fiction); Short stories; Nouvelles